2023
DOI: 10.7759/cureus.37931
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Histopathology in Abnormal Uterine Bleeding and Its Relation With Thyroid Profile and Endometrial Thickness

Abstract: Introduction: Abnormal uterine bleeding (AUB) is a common complaint in postmenopausal and perimenopausal women, caused by a range of disorders, including structural and systemic diseases. The evaluation of endometrial thickness (ET) via radiological methods, followed by a histopathological examination of the endometrium, is useful for proper diagnosis. Among systemic diseases, thyroid dysfunction, specifically hypothyroidism and hyperthyroidism, contribute significantly to AUB cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
0
0
Order By: Relevance
“…Similar findings were obsereved by other studies. [3][4][5][6][7][8][9]15 Hypertension is the most common co morbid condition that is associated with AUB in the present study which is a similar finding in Rajini Vaidya et al 1 study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar findings were obsereved by other studies. [3][4][5][6][7][8][9]15 Hypertension is the most common co morbid condition that is associated with AUB in the present study which is a similar finding in Rajini Vaidya et al 1 study.…”
Section: Discussionsupporting
confidence: 88%
“…3,[5][6][7][8][9][10][11][12][13] Functional causes (64.2%) of AUB are more common than organic causes (35.8%) in this study which is in concordance with study done by Sharma et al, 7 Vijayaraghavan et al, 3 Dwivedi et al, 9 Prathipa et al, 10 J Bindhuja et al, 12 Neha Khanam et al 15 Normal cyclical endometrium patterns are commonly seen in the present studywhich is similar to other studies. [3][4][5][6][7][8][9][10][11][12][13][14][15] Proliferative phase (34.7%) was the most common followed by secretory phase (18.9%) among all age groups of women in the present study.Similar findings were observed by Vijayaraghavan et al, 3 Jagadale Kunda et al, 5 Sharma et al 7 Disordered proliferative endometrium was seen in 5.83% of cases. Majority of the cases were in the age group of 18-40 years.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The present study also evinced that endometrial thickness ≥ 10 mm was an independent risk factor for AUB in perimenopausal women. Indeed, consistent with this result, a previous study [ 27 ] has showed that majority of women with AUB in aerimenopausal age had endometrial thickness of 10–12 mm (35.7%) followed by 7–9 mm (27.1%). Getpook et al [ 28 ] concluded that endometrial thickness of 8 mm or less was less likely to be associated with malignant pathologies in premenopausal uterine bleeding.…”
Section: Discussionsupporting
confidence: 86%
“…Thyroid disorders are more prevalent in women, especially during their reproductive years [5]. Having problems with your periods is often linked to hypothyroidism, which is marked by high levels of thyroidstimulating hormone (TSH) and low levels of free thyroxine (FT4) and free triiodothyronine (FT3) [6].…”
Section: Introductionmentioning
confidence: 99%